PENGARUH PENERAPAN APLIKASI TELEGRAM TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 1 PENUKAL UTARA - Juliani, Juliani; Ahyani, Nur; Nindiati, Dina Sri (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This research is motivated by the low score of students in the History subject in grade XI of SMA Negeri 1 Penukal Utara. The method used in this study is quantitative with the type of experiment and the design of the pretest-postest control group. The population used was 197 students with a total sample of 56 students consisting of class XI.1 totaling 28 students and class XI.2 totaling 28 students. Meanwhile, the data collection techniques used in this study consist of Observation, Tests and Documentation. The data analysis techniques used were normality tests, homegenity tests and hypothesis tests